Cereal price shocks and volatility in Sub-Saharan Africa: What does really matter for farmers' welfare? - Jean Balié; Emiliano Magrini; Cristian Morales Opazo (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2016)
After the 2007-08 food crisis, addressing high and volatile cereal prices became a priority for national governments in Sub-Saharan Africa because of their key role in determining consumption and income of poor smallholders. Nevertheless, the lack of information and some misperceptions on the distinction between the welfare consequences of higher versus more volatile cereal prices limited the effectiveness of policy interventions. Using household-level data, this paper empirically investigates the different effects of the two phenomena and provides an estimate of their magnitude and distributional consequences in four SSA countries over the period 2011-2012. The results show that the impacts of higher and more volatile prices on welfare heavily depend on the domestic structure of the economy. The most important factors to consider are the different weight of food consumption over total expenditure, the shares of the food budget devoted to cereals, the substitution effect among food items, and the relative number of net sellers versus net buyers accessing the market. We also find that the impact of higher substantially outweigh the effects of more volatile prices on farmers' welfare across the entire income distribution in all four countries. As a consequence, farmers are likely to benefit more from policy interventions preventing or limiting cereal price increases than (untargeted and extremely expensive) price stabilization policies. Nevertheless, our results also suggest that some targeted policy interventions aimed at reducing the exposure to cereal price volatility of the poorest quintile of the population is still required to protect them from substantial welfare losses.
Keywords: C31; D12; D13; Q12; 330; cereal price; price volatility; welfare; household survey; Sub-Saharan Africa